1998
DOI: 10.1103/physrevc.57.3484
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric and asymmetric nuclear matter in the relativistic approach at finite temperatures

Abstract: The properties of hot matter are studied in the frame of the relativistic Brueckner-Hartee-Fock theory. The equations are solved self-consistently in the full Dirac space. For the interaction we used the potentials given by Brockmann and Machleidt. The obtained critical temperatures are smaller than in most of the nonrelativistic investigations. We also calculated the thermodynamic properties of hot matter in the relativistic Hartree-Fock approximation, where the force parameters were adjusted to the outcome o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 25 publications
6
37
3
Order By: Relevance
“…Later, Brueckner calculations (Lejeune et al 1986;Baldo & Ferreira 1999) and chiral perturbation theory at finite temperature (Kaiser et al 2002) confirmed these findings with very similar values of T c . The Van der Waals behavior was also found in the finite-temperature relativistic Dirac-Brueckner calculations of Ter Haar & Malfliet (1986, 1987 and Huber et al (1999), although at a lower temperature.…”
Section: Eos Of Nuclear Matter At Finite Temperaturementioning
confidence: 57%
“…Later, Brueckner calculations (Lejeune et al 1986;Baldo & Ferreira 1999) and chiral perturbation theory at finite temperature (Kaiser et al 2002) confirmed these findings with very similar values of T c . The Van der Waals behavior was also found in the finite-temperature relativistic Dirac-Brueckner calculations of Ter Haar & Malfliet (1986, 1987 and Huber et al (1999), although at a lower temperature.…”
Section: Eos Of Nuclear Matter At Finite Temperaturementioning
confidence: 57%
“…[12] and T C ≃ 10MeV in Ref. [13]. One possible reason for this discrepancy is the difference between the relativistic effect in the DB approach [27] and the effect of the present microscopic TBF as discussed in Ref.…”
Section: Numerical Results and Discussionmentioning
confidence: 91%
“…Theoretically, considerable effort has been devoted to establishing the EOS of hot symmetric nuclear matter and discussing the critical phenomena [7][8][9][10][11][12][13]. Although almost all the predicted EOSs of infinite symmetric nuclear matter display a typical Van der Waals behavior, the obtained values of the critical temperature T C for the phase transition are distributed in a wide range from 8MeV to 20MeV.…”
Section: Introductionmentioning
confidence: 99%
“…Finite temperature Dirac-Brueckner calculations are quite few in the literature [3,4]. Furthermore, for our analysis we need the free energy as a function of density at small steps of the temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Phenomenological information on the EoS can be obtained from experimental data on heavy ion collisions at intermediate energies and astrophysical observations on supernovae explosions and neutron stars. The nuclear matter EoS is believed to go through a liquid-gas phase transition, as many theoretical calculations indicate [1][2][3][4]. However, if this phase transition exists, does not possess a direct correspondence in finite nuclei, due to the presence of the Coulomb and finite size effects.…”
Section: Introductionmentioning
confidence: 99%